Influence of A Novel Catalysis on The Pyrolysis Yields Obtained by Two Different Reactors - Mert Kılınçel; Ethem Toklu; Fikret Polat (Journal of Advanced Research in Natural and Applied Sciences)
In the present study mixtures of polymeric and cellulosic biomass materials were pyrolized in the presence of two different catalysts (sepiolite and aluminium bauxite) in various ratios by two different reactors; a rotary kiln reac-tor (RKR) and a fixed bed pyrolysis reactor (FBR). The results were compared to determine the effects of pyrolysis parameters such as catalysts, feedstock and reactor types on the energy content of the final products. First, the polymeric and cellulosic materials were mixed at certain ratios and thus the mixtures were prepared. Then, thermal-ly activated catalysts were added to these mixtures. At the end of the experiments, certain properties such as higher heating value (HHV), the elemental concentrations, particle size and size surface areas of the end products (for solid and liquid phases) were calculated and analysed. The HHV of the liquid products from bauxite added mix-ture in RKR and FBR was 42.74 MJ/kg and 40.95 MJ/kg respectively. Besides the HHV of the oil products from sepiolite added mixture in RKR and FBR was 41.28 MJ/kg and 38.94 MJ/kg respectively. These values are same and close to HHV of the conventional diesel (42.7 MJ/kg). However no considerable effect seen on HHV of char products from catalyst added mixtures. On the other hand, due to the SEM images the char products it can be clearly concluded that comparing with FBR, RKR had the better performance on pyrolysis of the biomass mix-tures